CD44 Glycosylation as a Therapeutic Target in Oncology - Liao, Chengcheng; Wang, Qian; An, Jiaxing; Chen, Jie; Li, Xiaolan; Long, Qian; Xiao, Linlin; Guan, Xiaoyan; Liu, Jianguo (Frontiers in Oncology, 2022)
Aberrant glycosylation is a hallmark of tumors, and glycosyl modifications of pivotal glycoproteins have been considered markers for tumor diagnosis and potential therapeutic targets. CD44 is a nonkinase transmembrane glycoprotein that is overexpressed in a variety of cell types, including cancer stem cells, with frequent alternative splicing variants, and it is thought to play a role in cancer development and progression. Changes in CD44 glycosylation can regulate its binding to HA, Siglec-15, fibronectin, TM4SF5, PRG4, FGF2, collagen and podoplanin and activate or inhibit c-Src/STAT3/Twist1/Bmi1, PI3K/AKT/mTOR, ERK/NF-κB/NANOG and other signaling pathways, thereby having a profound impact on the tumor microenvironment and tumor cell fate. However, the glycosylation of CD44 is complex and largely unknown, and the current understanding of how CD44 glycosylation affects tumors is limited. These issues must be addressed before targeted CD44 glycosylation can be applied to treat human cancers.